2022
DOI: 10.3389/fimmu.2022.872353
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Natural Killer Cells and Their Receptors/Ligands in Hepatocellular Carcinoma: A Systematic Review and Meta-Analysis

Abstract: BackgroundNatural killer (NK) cells play major roles in eliminating tumor cells. Preliminary studies have shown that NK cells and their receptors/ligands have prognostic value in malignant tumors. However, the relevance of NK cells and their receptors/ligands level to the prognosis of hepatocellular carcinoma (HCC) remains unclear.MethodsSeveral electronic databases were searched from database inception to November 8, 2021. Random effects were introduced to this meta-analysis. The relevance of NK cells and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…A meta-analysis showed that the percentage of infiltrating NK cells in HCC strongly correlates to a better patient outcome. 6 Furthermore, various in vitro and in vivo studies have identified NK cells and CD8 þ T lymphocytes as promising therapeutic targets in HCC. Among the various targets identified in previous studies, we focused on the NKG2D-MICA relationship based on our previous genome-wide association study data from chronic viral hepatitis, which demonstrated the critical role of MICA in hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis showed that the percentage of infiltrating NK cells in HCC strongly correlates to a better patient outcome. 6 Furthermore, various in vitro and in vivo studies have identified NK cells and CD8 þ T lymphocytes as promising therapeutic targets in HCC. Among the various targets identified in previous studies, we focused on the NKG2D-MICA relationship based on our previous genome-wide association study data from chronic viral hepatitis, which demonstrated the critical role of MICA in hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition, the percentage of infiltrating NK cells in HCC correlates with better patient outcomes. 6 Activation of members of the natural cytotoxicity receptor family, including NK group 2D (NKG2D), results in the release of preformed cytolytic granules containing granzyme B and perforin 3 . Furthermore, the relationship between membrane-bound NKG2D ligand (mNKG2DL) and its corresponding receptor, NKG2D, is essential for the effective elimination of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies suggested that NK cells can be educated during development, possess antigen-specific receptors, undergo clonal expansion and acquire immunological memory ( 53 ). Although high circulating NK cell count was associated with better OS in gastric cancer ( 23 ), the prognostic role of NK cells was conflicted in various cancers and warrant further study ( 54 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…124 In human HCC, high infiltration of NK cells has been shown to be associated with a favourable prognosis. 125,126 Moreover, NK cell frequencies in both peripheral blood and tumour tissue are decreased in patients with HCC. 127 In patients with HCC, a decrease in DC frequency was observed compared to healthy controls.…”
Section: Impairmentofnkcell Sand Subs E Tredis Tributioncontribute S ...mentioning
confidence: 99%